2021
DOI: 10.1561/2200000083
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Open Problems in Federated Learning

Abstract: Federated learning (FL) is a machine learning setting where many clients (e.g. mobile devices or whole organizations) collaboratively train a model under the orchestration of a central server (e.g. service provider), while keeping the training data decentralized. FL embodies the principles of focused data collection and minimization, and can mitigate many of the systemic privacy risks and costs resulting from traditional, centralized machine learning and data science approaches. Motivated by the explosive grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
1,429
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 2,480 publications
(1,437 citation statements)
references
References 154 publications
(225 reference statements)
3
1,429
0
5
Order By: Relevance
“…A comprehensive review of these challenges can be found in [6]. In particular, despite being recognized as one of the primary bottlenecks of FL [2], [6], [7], research on the communication aspect in the FL pipeline has not been on par with the overview. There are also recent studies that focus on the communication system design [8]- [10], but they are either system-specific (e.g., cellular networks) or with high complexity beyond the current implementation capability (e.g., very high dimensional vector quantization).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of these challenges can be found in [6]. In particular, despite being recognized as one of the primary bottlenecks of FL [2], [6], [7], research on the communication aspect in the FL pipeline has not been on par with the overview. There are also recent studies that focus on the communication system design [8]- [10], but they are either system-specific (e.g., cellular networks) or with high complexity beyond the current implementation capability (e.g., very high dimensional vector quantization).…”
Section: Introductionmentioning
confidence: 99%
“…The FL process typically includes the following steps [ 9 ]: Identifying a problem to be solved; Modifying the client’s application (optional); Simulating prototyping (optional); Training the federated model; Evaluating the federated model; Deploying FL at the server and clients. …”
Section: Federated Learning Conceptsmentioning
confidence: 99%
“…Based on how data are distributed, FL systems can typically be categorized as horizontal or vertical FL systems [ 9 , 10 , 24 ].…”
Section: Federated Learning Challengesmentioning
confidence: 99%
See 2 more Smart Citations